The Influence of Intellectual Capital and Islamicity Performance Index On Islamic Social Reporting Disclosures - Deanisa Wahyuantika; Nur Isna Inayati; Azmi Fitriati; Bima Cinintya Pratama (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the influence of Intellectual Capital and the Islamicity Performance Index on Islamic Social Reporting Disclosures. The research sample used Islamic commercial banks registered with the Financial Services Authority (OJK) for the 2009-2021 period. The sampling technique used purposive sampling and the number of research data was 154 data. Technical data analysis using multiple linear regression analysis using SPSS. The results of the hypothesis test show that the Profit-Sharing Ratio has a positive effect on ISR disclosure, this is because profit is a benchmark for the company's ability to make a profit. Where the profit shows that the company's financial condition is in a strong state so it tends to disclose a broader social accountability report. Zakat Performance Ratio has a positive influence on Islamic Social Reporting disclosure, this proves that the performance of Islamic banking can be seen from zakat activities managed by banks. For variable Equitable Distribution Ratio, Directors- Employees Welfare Ratio, Islamic Income vs Non-Islamic Income, and Islamic Investment vs non-Islamic investment do not affect the disclosure of ISR, this is because the distribution of income carried out by Islamic banks, the comparison of salaries of directors and employees, the comparison of income and halal or non-halal investments has no effect e disclosure of the social responsibility of Islamic banking. Intellectual Capital does not affect the disclosure of ISR, this shows that the utilization of the value of Islamic banking Intellectual Capital for ISR disclosure has not been maximized.